Therapeutic Potential of Menstrual Blood-derived Stem Cells in Attenuating Uterine Adhesion: Novel Strategies and Future Prospect - Rajabloo, Yasamin; Al-Asady, Abdulridha Mohammed; Avan, Amir; Khazaei, Majid; Ryzhikov, Mikhail; Hassanian, Seyed Mahdi (Current Pharmaceutical Design, 2025)
Intrauterine Adhesions (IUAs) are characterized by endometrial damage due to endometritis or curettage. Currently, the gold standard for IUA treatment is hysteroscopy, which enables the dissolution of IUA through mechanical or electrosurgical energy. Common strategies to prevent recurrence include the insertion of a balloon catheter or IUD in the uterus. Although hysteroscopy and postoperative strategies improve the uterine cavity’s morphology and menstrual flow in some patients, infertility and adhesion recurrence rates are among the problems that persist. Mesenchymal Stem Cells (MSCs) are ideal for tissue regeneration due to their self-renewal and immunomodulatory characteristics. MSCs also exert anti-fibrotic properties in IUA treatment. However, the clinical application of stem cells is limited due to safety concerns and cost. In this review, we have summarized the recent advances in the application of MSCs in IUA treatment.
Keywords: stem cell therapy; umbilical cord; bone marrow mesenchymal stromal cells (BMSCs)